1996
DOI: 10.1093/pasj/48.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Coronal Electron Temperature at the Total Solar Eclipse on 1994 November 3

Abstract: A spectroscopic observation was carried out at the total solar eclipse on 1994 November 3 in Putre, Chile, in order to investigate the electron temperature and the expanding motion of the corona. The shape of weak depressions at 3900 Å and 4300 Å in the continuous coronal spectra was compared with the theoretical electron-scattered coronal spectra; thus, the magnitude of the electron thermal motion was determined directly. It was found that a coronal streamer on the eastern limb and a coronal hole on the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 3 publications
1
22
0
1
Order By: Relevance
“…Earlier attempts using electron-based measurements include Grall et al (1996), using interplanetary radio scintillation measurements, and Fineschi et al (1998), using Ly α profiles obtained from observations through the Ultraviolet Coronagraph Spectrometer (UVCS) onboard the Solar and Heliospheric Observatory (SOHO). Ichimoto et al (1996) obtained a measurement also based on electron scattering. Reginald et al (2003) reported spectroscopic measurements at several locations in the K-corona from measurements obtained during the 2001 eclipse in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts using electron-based measurements include Grall et al (1996), using interplanetary radio scintillation measurements, and Fineschi et al (1998), using Ly α profiles obtained from observations through the Ultraviolet Coronagraph Spectrometer (UVCS) onboard the Solar and Heliospheric Observatory (SOHO). Ichimoto et al (1996) obtained a measurement also based on electron scattering. Reginald et al (2003) reported spectroscopic measurements at several locations in the K-corona from measurements obtained during the 2001 eclipse in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…The electron density model used by Cram (1976), in formulating the properties of the K-coronal intensity spectrum for the determination of the thermal electron temperature in the corona, is given in Equation (4): Ichimoto et al (1996) used the same electron density model given in Equation (4) in determining the coronal electron temperatures. Their eclipse observation of November 1994 coincided with the Sun at its minimum phase where the coronal brightness is prominently displayed in an elongated shape in the equatorial regions of the Sun.…”
Section: Influence Of Electron Density On the K-coronal Spectrummentioning
confidence: 99%
“…This model is appropriate for the temperature determination by Ichimoto et al (1996) because their observations were confined to regions between 1.5R and 2.0R and also their observations on the total solar eclipse of November 1994 coincided with the minimum phase of the Sun.…”
Section: Influence Of Electron Density On the K-coronal Spectrummentioning
confidence: 99%
See 2 more Smart Citations